Childhood Maltreatment, Stressful Life Events, and Alcohol Craving in Adult Drinkers. (24th June 2014) - Kim, June H.; Martins, Silvia S.; Shmulewitz, Dvora; Santaella, Julian; Wall, Melanie M.; Keyes, Katherine M.; Eaton, Nicholas R.; Krueger, Robert; Grant, Bridget F.; Hasin, Deborah S.
<x xml:space="preserve">Abstract</x> Background Little is known about the relationship between stressful life events and alcohol craving in the general population, and whether a history of childhood maltreatment sensitizes individuals to crave alcohol after adult stressors. Methods Participants were 22, 147 past‐year drinkers from Wave 2 (2004 to 2005) of the National Epidemiologic Survey on Alcohol and Related Conditions. A structured, face‐to‐face interview assessed past‐year stressful life events, alcohol craving, and history of childhood maltreatment. Logistic regression was used to generate adjusted odds ratios (aOR) to evaluate the relationship between stressful life events and craving, adjusting for demographic characteristics and parental history of alcoholism. Interaction between stressful life events and childhood maltreatment was also assessed. Results Compared to participants with no stressful life events, those with ≥3 events had increased odds of moderate alcohol craving (aOR = 3.15 [95% CI = 2.30 to 4.33]) and severe craving (aOR = 8.47 [95% CI = 4.78 to 15.01]). Stressful life events and childhood maltreatment interacted in predicting severe craving (p = 0.017); those with ≥3 events were at higher risk of craving if they had been exposed to childhood maltreatment. Conclusions A direct relationship between stressful life events and risk of alcohol craving was observed. Further, history of childhood maltreatment increased the salience of stressful life events in adulthood. Future studies should examine the role of psychiatric comorbidity in more complex models of stress sensitization and alcohol craving.